PENGARUH PEMBAGIAN TUGAS DAN KETERAMPILAN TERHADAP HASIL KERJA KARYAWAN PERKEBUNAN KOPI PT. RERO LARA HOKENG - Liwu, Gasparin Paen; Mea, Maria Helena Carolinda Dua (ANALISIS, 2025)
The purpose of this study is to determine and analyze the effect of task division on the work results of PT. Rero Lara Hokeng employees and to determine and analyze the effect of work skills on the work results of PT. Rero Lara Hokeng employees. This study is a quantitative study with a survey method. This study was conducted at PT. Rero Lara Hokeng Jalan Trans Maumere-Larantuka, Wulanggitang District, East Flores Regency. The sampling method used in this study was saturated sampling totaling 120 employees. Data collection in this study was carried out by distributing questionnaires. The results of multiple linear regression analysis showed that there was a positive and significant effect between the variable of task division on the work results of PT. Rero Lara Hokeng coffee plantation employees with a t-count value of 3.918, meaning t count> t table 1.98045 and a significant value of 0.000 <0.05. 2; there is a positive and significant effect between the variable of employee skills on the work results of PT. Rero Lara Hokeng with a t-value of 2.767 means t count> t table 1.98045 and a significant value of 0.010 <0.05, it can be concluded that the hypothesis is accepted and proven.